SELEKSI POHON PLUS PADA UJI KETURUNAN Shorea leprosula DI KALIMANTAN TENGAH - Abdurrani Muin; Oktiariana Rini Lestari; Reine Suci Wulandari (Jurnal Pemuliaan Tanaman Hutan, 2021)
The progeny trial of Shorea leprosula was established in Central Kalimantan under the IUPHHK-HA management of PT. Erna Djuliawati by planting 30 families to examine the genetic superiority of  trees as plywood raw material. The trial was laid-out using  8 blocks, 4 tree-plots and a spacing of 6 x 3 m. The aim of the study was to practice the plus trees selection in the progeny trial. The study was conducted using a survey method on phenotypically superior trees based on a diameter at breast height (dbh) baseline of ≥ 30 cm. The data collected and analyzed for the plus trees and comparison trees were total tree height (m), dbh (cm), and dbh increment (cm/yr). The results of the initial selection showed that 110 trees from 29 families were selected as candidate plus trees in the progeny trial. Futhermore, the honest significant difference test (BNJ) and scoring showed that there were 15 trees from 9 families that can be designated as plus trees.